Prince Sabahattin (1878-1948) and his place in Ottoman intellectual development - Helvacı, Pelin. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
This thesis examines Prince Sabahattin’s place in Ottoman intellectual development that started to flourish in Tanzimat era. Prince Sabahattin is portrayed with his intellectual capacity, besides his stance in politics as a liberal and his lead in social sciences. As an intellectual, Prince Sabahattin was misunderstood in his own period due to his close association to Anglo-Saxon system with decentralization and private initiative issues that were pillars of liberalism. Although he did not involve actively in politics, he influenced the formation of opposition party, Ahrar (Liberal Party). But his main impact was putting individual development to the core for the advancement of the society, which, according to him, was possible only by inner dynamics, rather than applying top-down reforms. For this, he outlined a social program, Meslek-i İçtimai (Profession of Sociology), which was the first attempt to look for the solutions of social problems, like administration, education and village development in a systematic way that he learned from the French sociologist, Le Play. In this program, which was shaped around the belief in the superiority of Anglo-Saxon system, he emphasized the importance of individualistic form of society, rather than communitarian one and put the British type of education to the core, which led the prospering of individual by himself rather than kinship ties or community bonds for the advancement of society. The Village Institutes of the 1940s could be traced back him, since he was the first one to mention the importance of village development, which became one of the main issues in 1940s. Although his lack of knowledge of Ottoman society could not be ignored because of his belonging to the Ottoman dynasty, as a son of Mahmud Celaleddin Paşa and Seniha Sultan (Abdulhamid II’s sister), compared to his contemporaries, his program was a permanent and a projectionist one, which left an imprint in both Turkish politics and social sciences.